Розробка інформаційної навчальної cиcтеми «аctive english» для вивчення англійcької мови - Козаченко, Є. Д. (ХНУРЕ, 2022)
This work is devoted to creation of the information educational system for quick and efficient self-study of English. In the process of work the methods of increasing the efficiency of learning English and the ways of their realization are proposed, the essence of the principle of gradual complication of tasks and a method of rational repetition of material (with the substantiation of its efficiency as a tool for memorizing information) is stated. Direction of further development: expansion of the functional part of the application, creation of a web version and software for mobile devices.